Consecuencias sociales producidas por la migración derivada de la crisis económica y política del ecuador (periodo 1999-2000), en la comunidad de San José de la Tranca perteneciente a la Provincia del Cañar, al año 2019 - Calle Calle, Vilma Guadalupe (2021)
Introduction: One of the measures taken by the Ecuadorian population at the end of the nineties was to flee the country, leaving their loved ones in search of better days.Objective: To determine the social consequences produced by migration derived from the economic and political crisis in Ecuador (period 1999-2000), in the community of San José de la Tranca belonging to the province of Cañar, through a critical analysis, in order to point out causes and consequences. The methodology corresponds to a historical study, carried out under a qualitative approach; non-experimental, cross-sectional ethnographic design. The deductive, inductive and analytical method were applied. The data were obtained with the application of a survey and an interview, considering a population made up of 10 migrants from the locality and two experts on the subject. Conclusion: The main social consequences after the massive departure of the residents of San José de la Tranca community were family disintegration, the appearance of public health problems in the adolescent population and the loss of cultural identity.